Call Me Maybe… A Simulation Based Curriculum for Telephone Triage Education in a Pediatric Residency - Blumberg, Joel S.; Barajaz, Michelle; Roberts, Danielle; Clary, Cody; Kumar, Shelley (Frontiers in Pediatrics, 2020)
Pediatrician communication with caregivers by phone has traditionally made a significant impact on patient care but remains a source of medical liability. Despite its importance, few publications exist regarding the education of pediatric residents on telephone triage. Kolb’s experiential learning theory describes the building of knowledge via reflection upon concrete experience, generalization of knowledge gained, and application of this knowledge. For telephone triage, simulation allows for direct observation of pediatric residents as they develop this skill. It also provides a concrete experience on which learners build the foundation of their learning. Our educational strategy was based on Kolb’s learning theory and the Kern approach to curriculum development. This involved simulation, resource familiarization, didactic education, and application of skills with the goal of skill expansion in telephone triage. In a 30-minute PowerPoint presentation, instructors reviewed the basic tenets of telephone triage. The learner was expected to utilize skills gained in a simulated primary care setting and reinforce the content with spaced repetition. In the pilot study, residents were divided into two groups and performance was monitored during two scripted, symptom based “parent” phone call simulations. One group received the PowerPoint didactic prior to the simulation, and the other group received the didactic after simulation. A comparison of resident evaluations by faculty and self-documented confidence level revealed statistically significant higher evaluation scores in the didactic-first group, and an overall improvement in resident confidence with telephone triage. We conclude that this educational curriculum may improve pediatric resident performance in telephone triage.